Simone de Beauvoir’s Case for Philosophical Autonomy and the Possibilities within the Metaphysical Novel - Katz, Juliana de Albuquerque (Sapere Aude, 2013)
The work intends to prove a case of Beauvoir's autonomy in relation to Sartre by offering an account of the fundamental role that Literature, Philosophy and their liaison, played on her development as a philosopher whose intellectual production has an importance of its own. O presente trabalho tem por objetivo apresentar uma defesa da autonomia intelectual de Simone de Beauvoir em relação ao pensamento de Jean-Paul Sartre. Para isso, será feita uma breve análise do papel que literatura e filosofia possuem no desenvolvimento da obra beauvoariana, demonstrando que a sua produção intelectual carrega em si uma importância própria.